A guide for the design of functional polyaromatic organophosphorus materials - Hindenberg, Philip; Rominger, Frank; Romero-Nieto, Carlos (Chemistry - a European journal, 2017)
The impact of integrating six-membered phosphorus heterocycles into a poly(hetero)aromatic materials is investigated. Mechanistic studies reveal the key synthetic requirements to embed the latter phosphorus heterocycles in polyaromatic molecules. DFT calculations indicate that introducing six-membered phosphorus rings into π-extended molecules induces a particular electron distribution over the π-extended system. Electrochemical investigations confirm that inserting six-membered phosphacycles into polyaromatics triggers ambipolar redox behavior. Steady-state spectroscopy reveals that fusing pyrroles with phosphorus-containing polyaromatic molecules induces fluorescence quantum yields as high as 0.8, whereas transient absorption spectroscopy demonstrates that fusing thiophenes promote the formation of non-emissive triplet-excited states. As a whole, the optoelectronic properties of fused phosphorus-containing materials give rise to promising performances in photoelectrochemical cells. Moreover, X-ray analyses confirm that the 3D arrangement in the solid state of polyaromatic systems containing six-membered phosphorus rings can be tailored through post-functionalization of the phosphorus center. Altogether, this investigation sets the bedrock for the design of a new generation of highly functional polyaromatic organophosphorus materials, keeping control over their electrochemical properties, fluorescence features, photo-induced excited states, and 3D molecular arrangement.